Identification of the Natural Product Rotihibin A as a TOR Kinase Signaling Inhibitor by Unbiased Transcriptional Profiling. Issue 48 (27th July 2018) - Halder, Vivek; Oeljeklaus, Julian; Heilmann, Geronimo; Krahn, Jan H.; Liu, Yanlin; Xiong, Yan; Schlicht, Markus; Schillinger, Jasmin; Kracher, Barbara; Ehrmann, Michael; Kombrink, Erich; Kaschani, Farnusch; et al.
Abstract: Bioactive natural products are important starting points for developing chemical tools for biological research. For elucidating their bioactivity profile, biological systems with concise complexity such as cell culture systems are frequently used, whereas unbiased investigations in more complex multicellular systems are only rarely explored. Here, we demonstrate with the natural product Rotihibin A and the plant research model system Arabidopsis thaliana that unbiased transcriptional profiling enables a rapid, label‐free, and compound economic evaluation of a natural product′s bioactivity profile in a complex multicellular organism. To this end, we established a chemical synthesis of Rotihibin A as well as that of structural analogues, followed by transcriptional profiling‐guided identification and validation of Rotihibin A as a TOR signaling inhibitor (TOR=target of rapamycin). These findings illustrate that a combined approach of transcriptional profiling and natural product research may represent a technically simple approach to streamline the development of chemical tools from natural products even for biologically complex multicellular biological systems. Abstract : Assigning bioactivities in complex multicellular organisms : By using a combination of natural product synthesis, unbiased transcriptional profiling, and bioassays, the natural product Rotihibin A was identified as a TOR signaling inhibitor in Arabidopsis (TOR=target of rapamycin; see figure).